Solar Electricity Generating Technology as a Power Supply Automatication of Deep Well Water Pumps in Gunungkidul, Indonesia - Umi Salamah; Qonitatul Hidayah; Sri Handayaningsih; Damar Yoga Kusuma; Apik Rusdiarna Indra Praja (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
Water is a vital human need that must be met for human survival and carrying out daily activities. However, the condition of natural resources in each region is different, not all regions have sufficient water availability. One of them is in Serut, Gunungkidul which is an area with hilly geography. During the dry season, clean water sources in Serut District become scarce and very limited. Therefore, the Serut District Government cooperates with the Community Self-Help Group (KKM Tirta Abadi Jaya) to drill deep wells to distribute water to residents. However, along the way, the operational costs are very large, especially for water pump electric pulses. In addition, the geographical condition of Serut which is hilly and has many trees causes frequent power outages, especially in extreme weather. This affects the resistance of the water pump because it is often on and off. The power outage can also stop the distribution of water to residents. This community service provides a solution to these problems, namely the installation of solar electricity generation. With this solar electricity generation, it can reduce the operational costs of electric pulses. In addition, using solar electricity generation can increase the durability of the tool because there is no on-off. Residents also still have their water needs met even though there is a power outage because the electricity needs for water pumps are supplied from solar electricity generation.